Đề xuất quy trình dạy học đọc hiểu thơ Đường luật cho học sinh trung học phổ thông theo định hướng phát triển năng lực - Đặng, Thị Ngọc Lan (Tạp chí Giáo dục, 2025)
In the 2018 General Education Program for Literature, Tang poetry plays a vital role in forming and developing the competence to read and understand literary texts for high school students. As a typical poetic form of medieval lyric poetry, Tang poetry has unique artistic value and is an essential part of the national literary treasure. In particular, in the Grade 10 Literature program, this poetic form is a typical model for students to approach Vietnamese classical literature. However, in teaching practice, Tang poetry is often considered difficult to approach due to its specific rules, ancient language, contemporary factors, and complex content-artistic structure. Faced with these challenges, this article proposes a process for teaching and understanding Tang poetry competency-based, aiming to support teachers in solving difficulties and improving the effectiveness and quality of teaching this genre in schools today. Thereby, the article provides a specific and feasible pedagogical orientation; at the same time, it contributes to affirming the role of Tang poetry in aesthetic education and fostering language and thinking skills for students.